2018
DOI: 10.1089/jop.2017.0095
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Clinical Efficacy of Topical and Systemic Azithromycin Treatment for Posterior Blepharitis

Abstract: Although both treatment methods are found to be effective, the results of topical treatment group showed some superiority over those of systemic treatment group, which may be associated with a higher ocular tissue concentration of azithromycin after topical administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 26 publications
0
47
0
Order By: Relevance
“…Five RCTs were conducted to evaluate the effects of azithromycin ophthalmic solutions for resolving ocular signs and symptoms due to different eye diseases. Four of the five studies took subjects with blepharitis (7,(17)(18)(19) and one study reported the effect of azithromycin on patients with papulopustular rosacea (8). The efficacy of azithromycin on different clinical signs and symptoms is presented as follows.…”
Section: Study Description Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Five RCTs were conducted to evaluate the effects of azithromycin ophthalmic solutions for resolving ocular signs and symptoms due to different eye diseases. Four of the five studies took subjects with blepharitis (7,(17)(18)(19) and one study reported the effect of azithromycin on patients with papulopustular rosacea (8). The efficacy of azithromycin on different clinical signs and symptoms is presented as follows.…”
Section: Study Description Of Included Studiesmentioning
confidence: 99%
“…Four of the studies (7,8,17,19) reported the clinical efficacy of Azithromycin ophthalmic solutions in improving eyelid finding scores. The standardized mean difference of these studies indicates that there is statistically significant improvement in the severity of eyelid finding scores (RR = -1.94; 95%…”
Section: Eyelid Finding Scoresmentioning
confidence: 99%
See 3 more Smart Citations